Novel perspectives for hepatitis A virus therapy revealed by comparative analysis of hepatitis C virus and hepatitis A virus RNA replication - Esser-Nobis, Katharina; Harak, Christian; Schult, Philipp; Kusov, Yuri; Lohmann, Volker (Hepatology, 2015)
Hepatitis A virus (HAV) and hepatitis C virus (HCV) are two positive-strand RNA viruses sharing a similar biology, but causing opposing infection outcomes, with HAV always being cleared and HCV establishing persistence in the majority of infections. To gain deeper insight into determinants of replication, persistence, and treatment, we established a homogenous cell-culture model allowing a thorough comparison of RNA replication of both viruses. By screening different human liver-derived cell lines with subgenomic reporter replicons of HAV as well as of different HCV genotypes, we found that Huh7-Lunet cells supported HAV- and HCV-RNA replication with similar efficiency and limited interference between both replicases. HAV and HCV replicons were similarly sensitive to interferon (IFN), but differed in their ability to establish persistent replication in cell culture. In contrast to HCV, HAV replicated independently from microRNA-122 and phosphatidylinositol 4-kinase IIIα and β (PI4KIII). Both viruses were efficiently inhibited by cyclosporin A and NIM811, a nonimmunosuppressive analog thereof, suggesting an overlapping dependency on cyclophilins for replication. However, analysis of a broader set of inhibitors revealed that, in contrast to HCV, HAV does not depend on cyclophilin A, but rather on adenosine-triphosphate-binding cassette transporters and FK506-binding proteins. Finally, silibinin, but not its modified intravenous formulation, efficiently inhibited HAV genome replication in vitro, suggesting oral silibinin as a potential therapeutic option for HAV infections. Conclusion: We established a cell-culture model enabling comparative studies on RNA replication of HAV and HCV in a homogenous cellular background with comparable replication efficiency. We thereby identified new host cell targets and potential treatment options for HAV and set the ground for future studies to unravel determinants of clearance and persistence. (Hepatology 2015;62:397-408